2021
DOI: 10.1007/978-981-16-3611-0
|View full text |Cite
|
Sign up to set email alerts
|

Electricity Access and Community Welfare in Indonesia

Abstract: translation, reprinting, reuse of illustrations, recitation, broadcasting, reproduction on microfilms or in any other physical way, and transmission or information storage and retrieval, electronic adaptation, computer software, or by similar or dissimilar methodology now known or hereafter developed. The use of general descriptive names, registered names, trademarks, service marks, etc. in this publication does not imply, even in the absence of a specific statement, that such names are exempt from the relevan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 0 publications
2
5
0
Order By: Relevance
“…It caused that good budgetary management meets its objectives, for examples, the provision of basic services highly needed by the community (health infrastructure). These findings are also consistent with previous studies, concluding that the government ability to build and provide infrastructure was proven to significantly improve the quality of life of the community [12], [19], including the domains of psychological health, physical health, well-being, socio-cultural aspects, and environmental conditions [14], [15], [45]. However, this study does not support the findings of previous studies which concluded that village funds did not have a significant effect on improving village development and the quality of life of the community [15], [21].…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…It caused that good budgetary management meets its objectives, for examples, the provision of basic services highly needed by the community (health infrastructure). These findings are also consistent with previous studies, concluding that the government ability to build and provide infrastructure was proven to significantly improve the quality of life of the community [12], [19], including the domains of psychological health, physical health, well-being, socio-cultural aspects, and environmental conditions [14], [15], [45]. However, this study does not support the findings of previous studies which concluded that village funds did not have a significant effect on improving village development and the quality of life of the community [15], [21].…”
Section: Discussionsupporting
confidence: 91%
“…These findings are also consistent with previous studies, concluding that the government ability to build and provide infrastructure was proven to significantly improve the quality of life of the community [12], [19], including the domains of psychological health, physical health, well-being, socio-cultural aspects, and environmental conditions [14], [15], [45]. However, this study does not support the findings of previous studies which concluded that village funds did not have a significant effect on improving village development and the quality of life of the community [15], [21]. Government spending on health, such as the provision of health resources, did not have any effect on increasing the health quality and life the population either [22], [23].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Indonesia has had one of the breakthroughs through the Ministry of Maritime Affairs and Fisheries (KKP) with the development of export-based aquaculture with shrimp as one of the leading commodities (Nugroho et al, 2022). In 2014, total production from the world aquaculture sector reached 167.2 million tons, which was 64.15% of the total production in the fisheries sector which reached 260.6 million tons (Halimatussadiah et al, 2020;Sambodo et al, 2021). Shrimp cultivation is a commodity resulting from aquaculture businesses in ponds that needs to be improved both in quality and quantity.…”
Section: Introductionmentioning
confidence: 99%